2020
DOI: 10.21468/scipostphyscore.3.2.006
|View full text |Cite
|
Sign up to set email alerts
|

Density resolved wave packet spreading in disordered Gross-Pitaevskii lattices

Abstract: We perform novel energy and norm density resolved wave packet spreading studies in the disordered Gross-Pitaevskii (GP) lattice to confine energy density fluctuations. We map the locations of GP regimes of weak and strong chaos subdiffusive spreading in the 2D density control parameter space and observe strong chaos spreading over several decades. We obtain a renormalization of the ground state due to disorder, which allows for a new disorder-induced phase of disconnected insulating puddles of matter due to Li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The BdG equations are particle-hole symmetric [λ ν , {χ ν , Π ν }] ←→ [−λ ν , {Π ν , χ ν }] (ν is the mode number). This yields the solution χ = Π ∝ G l for λ ν = 0 as follows also readily from inspecting (24), independently of the choice of the GS field. The eigenvector to λ = 0 can be also obtained from the observation that δ is time-independent by Eq.…”
Section: Elementary Excitationsmentioning
confidence: 67%
See 2 more Smart Citations
“…The BdG equations are particle-hole symmetric [λ ν , {χ ν , Π ν }] ←→ [−λ ν , {Π ν , χ ν }] (ν is the mode number). This yields the solution χ = Π ∝ G l for λ ν = 0 as follows also readily from inspecting (24), independently of the choice of the GS field. The eigenvector to λ = 0 can be also obtained from the observation that δ is time-independent by Eq.…”
Section: Elementary Excitationsmentioning
confidence: 67%
“…By fixing the norm density, we numerically minimize the energy by varying the real and nonnegative variables G for a given disorder realization as in Ref. [24] (see also Appendix A). The resulting ground-state density distribution G 2 is plotted in Fig.…”
Section: Ground State Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [22,23,24,25,26,28,29,30,31,32,33,34] it was shown that Anderson localization is destroyed by the presence of nonlinearity, resulting to the subdiffusive spreading of energy due to deterministic chaos. Such results rely on the accurate, long time integration of the systems' equations of motion and variational equations.…”
Section: Introductionmentioning
confidence: 99%
“…Treating infinite particle numbers with mean-field approximations results in nonlinear add-ons to the wave dynamics which stem from the two-body interactions. Nonlinear wave packet expansion was investigated both analytically and numerically over vast time scales [26][27][28][29][30][31]. It allows to obtain the details of the subdiffusion process, with expansion times which are many orders of magnitude larger than comparable experimental simulations [32].…”
mentioning
confidence: 99%